Research Progress on the Mechanism of Histone Deacetylases in Ferroptosis of Glioma - Ma, Meng; Fei, Xifeng; Jiang, Dongyi; Chen, Hanchun; Xie, Xiangtong; Wang, Zhimin; Huang, Qiang (Oncology Reviews, 2024)
Glioma is the most prevalent primary malignant tumor of the central nervous system. While traditional treatment modalities such as surgical resection, radiotherapy, and chemotherapy have made significant advancements in glioma treatment, the prognosis for glioma patients remains often unsatisfactory. Ferroptosis, a novel form of programmed cell death, plays a crucial role in glioma and is considered to be the most functionally rich programmed cell death process. Histone deacetylases have emerged as a key focus in regulating ferroptosis in glioma. By inhibiting the activity of histone deacetylases, histone deacetylase inhibitors elevate acetylation levels of both histones and non-histone proteins, thereby influencing various cellular processes. Numerous studies have demonstrated that histone deacetylases are implicated in the development of glioma and hold promise for its treatment. This article provides an overview of research progress on the mechanism by which histone deacetylases contribute to ferroptosis in glioma.